2004
DOI: 10.1590/s0100-879x2004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial symptoms in dysmotility-like functional dyspepsia are not related to disturbances of gastric myoelectrical activity

Abstract: Gastric dysrhythmias, such as tachy-or bradygastria, have been reported in patients with functional dyspepsia (FD), but their role in symptom production is uncertain. It is also not known whether gastric dysrhythmias in these patients can be elicited by physiological gastric distension with a meal. We investigated the relationships between symptoms after ingestion of different volumes of water following a test meal and gastric dysrhythmias in FD patients. Fourteen patients with dysmotility-like FD and 13 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…The presence of abnormal ECA propagation patterns was found to be associated with gastric outlet obstruction (Brzana et al 1998, Smith et al 2003, gastroparesis (Smith et al 2003), gastric myoelectrical dysrhythmia (Qian et al 2003), atrophy and hypertrophy (Bortoff and Sillin 1986), diabetic gastropathy (Koch 2001) and Chagas disease (Madrid et al 2004), although no statistically significant differences were found between normal and abnormal EGG-recorded ECA patterns for human cases of achalasia (Verhagen et al 1998) and dysmotility-like functional dyspepsia (Oba-Kuniyoshi et al 2004, van der Voort et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of abnormal ECA propagation patterns was found to be associated with gastric outlet obstruction (Brzana et al 1998, Smith et al 2003, gastroparesis (Smith et al 2003), gastric myoelectrical dysrhythmia (Qian et al 2003), atrophy and hypertrophy (Bortoff and Sillin 1986), diabetic gastropathy (Koch 2001) and Chagas disease (Madrid et al 2004), although no statistically significant differences were found between normal and abnormal EGG-recorded ECA patterns for human cases of achalasia (Verhagen et al 1998) and dysmotility-like functional dyspepsia (Oba-Kuniyoshi et al 2004, van der Voort et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jebbink et al (12) found no significant difference between the patients in FD and the control groups with respect to the incidence of dysrhythmia. Similarly, Oba-Kuniyoshi et al (13) in their study on the dysmotility-like FD patients, reported no significant difference between the FD patients and the control subjects in terms of dysrhythmia. Inconsistency among the results of the studies may be caused by the fact that they have been conducted on patients with different diagnoses and that the diagnostic criteria for FD may vary.…”
Section: Discussionmentioning
confidence: 87%
“…Although much improvement has been made in the EGG field within the last twenty years, difficulties experienced in the recording of myoelectrical activity and analysis of the obtained signals still persist (9). Some studies have revealed statistically significant differences between the patients with FD and healthy control groups with respect to EGG parameters (6,11), while some others have not (12,13). On the other hand, Pfaffenbach et al (14) have detected a significant difference only in preprandial dysrhythmia whereas no postprandial difference has been detected.…”
Section: Introductionmentioning
confidence: 99%
“…In a Brazilian study using electrogastrography (EGG) in patients with motilitylike FD, disturbances of myoelectrical activity were not related to the occurrence of postprandial discomfort and bloating [45].…”
Section: Role Of Food Intolerance and Other Mechanisms In Postprandiamentioning
confidence: 92%